School Principals' Learning Strategies in the Knowledge society - Claudia NAVARRO-CORONA (Ediciones Universidad de Salamanca, 2017)
The demand for specialized profiles, typical of the knowledge society, has permeated Latin American educational systems, which is why evaluation systems have been established that seek to guarantee specific qualities in professors and scholar principals. The directive function has been recognized in educational research as a relevant activity for school functioning and indirectly for educational results; nevertheless, in the case of some educational systems, for example, the Mexican one, there are few formal offers for preparation in this function. In this framework, the objective of this paper is to identify the training mechanisms that directors use, as well as the knowledge they acquire through these ones. Through qualitative research conducted through interviews with directors and authorities of the Mexican educational system, it was found: 1) through assisted learning processes and learning in practice, in which the directors rely on nearby figures to acquire knowledge about their work; and 2) in self-adhered processes such as the observation and re-elaboration of management models, strategies of inquiry, trial and error and consultation of materials, principals apprehend to identify and solve problems, relate to others, adapt to contexts and manage school documentation. It is concluded that the essential knowledge of the directive function is acquired in the field of work, so it is recommended to redesign the training schemes that are focused on the action.